Functional MRI detects posterior shifts in primary sensorimotor cortex activation after stroke: evidence of local adaptive reorganization? - Pineiro, R; Pendlebury, S; Johansen-Berg, H; Matthews, P (2001)
BACKGROUND AND PURPOSE: Further recovery from stroke can occur late, long after the end of the apparent evolution of pathological changes. This observation and evidence obtained from functional imaging for altered patterns of activation after brain injury suggest that cortical reorganization may contribute to recovery. Here, we have tested for potentially adaptive reorganization in the primary sensorimotor cortex. METHODS: We used functional MRI to study brain activation with dominant hand movement in right-handed healthy control subjects (n=20) and in patients after subcortical ischemic infarcts causing mild to moderate right hemiparesis (n=8). The numbers of pixels activated above threshold and the geometric centers of activation clusters were determined. RESULTS: Although random-effects analysis identified some differences in activation maxima, similar regions of the brain were activated with sequential finger tapping in the patient and control groups. However, consistent with the heterogeneity in the locations, sizes, and times after the infarcts, patterns and magnitudes of activation showed some heterogeneity between patients. Nonetheless, for the group as a whole, there was a decreased motor cortex lateralization index (-0.1+/-0.7 in patients and 0.7+/-0.3 in control subjects, P=0.05). The geometric center of activation of the primary sensorimotor cortex activation cluster contralateral to the affected hand in patients was also shifted posteriorly (mean 12 mm, P<0.04) relative to that of the control subjects. To confirm the latter observation, the activation response with a simple hand-tapping task was examined in some of the subjects. With this task, there was also a trend (mean 10 mm, P=0.07) toward a more posterior activation in patients. CONCLUSIONS: These results confirm altered patterns of activation in the contralateral and ipsilateral primary sensorimotor cortices after recovery from strokes causing hemiparesis. These (and other changes) suggest that modulation of widely distributed parts of the cortical network for motor control may contribute to adaptations leading to functional recovery after stroke.